Slick potassium channels limit TRPM3-mediated activation of sensory neurons - Engel, Patrick; Zhou, Fangyuan; Tran, Bang Tam Thi; Schmidtko, Achim; Lu, Ruirui (Frontiers in Pharmacology, 2024)
Heat sensation is mediated by specialized heat-sensitive neurons in the somatosensory system that innervates the skin. Previous studies revealed that noxious heat sensation is controlled by the sodium (Na + )-activated potassium (K + ) channel Slick (Kcnt2), which is highly expressed in nociceptive Aδfibers. However, the mechanism by which Slick modulates heat sensation is poorly understood. Here, we generated mice lacking Slick conditionally in sensory neurons expressing Nav1.8 (SNS-Slick -/- mice). In SNS-Slick -/-mice, the latency to express any nocifensive behavior was reduced in the hot plate and tail immersion tests. In situ hybridization experiments revealed Slick was highly co-expressed with the essential heat sensor, transient receptor potential (TRP) melastatin (TRPM) 3, but not with TRP vanilloid 1, TRP ankyrin 1, or TRPM2 in sensory neurons. Notably, SNS-Slick -/-mice exhibited increased nocifensive behaviors following the intraplantar injection of the TRPM3 activator pregnenolone sulfate. Patch-clamp recordings detected increased Na + -dependent outward K + current (IK) after TRPM3 activation in sensory neurons, which showed no prominent IK after the replacement of NaCl with choline chloride. Thus, our study suggests that Slick limits TRPM3-mediated activation of sensory neurons, thereby inhibiting noxious heat sensing.